Software for Simulation of Bulk Media Forces on an Excavation Tool - Ahmad Hemami (Canadian Institute of Mining, Metallurgy and Petroleum, 2013)
A working code is developed to simulate the forces that are involved in the process of penetration of a bucket into bulk media during loading and excavation. The result of this work can be integrated with the simulation software that many manufacturers of heavy earthmoving machines introduce for training purposes. The simulator programs for machines such as backhoes, loaders, LHDs and the like, used for operator training, are usually only based on the kinematics of the machine. As a result, there is no indication of the effect of the medium when the cutting tool of such a machine touches the excavation material. This is like moving the machine in the air. Feeling the resistance force of medium to cutting by a bucket or blade during loading and excavation is more realistic, both mentally (by vision) and physically (feeling resistance in pedals and levers). The results from force simulation can be used by feedback in creating simulated resistance in these training gears, similar to what is done in flight simulators for aircrafts. In addition to serving for the above purpose, the results of this work can be used as a tool for examination and verification of the effect of a control policy for automation of loading and excavation of bulk media. So far no commercial product has been introduced that has such a capability, despite some extensive research on the subject.